The role of Imam Sadiq  In establishing the parameters of Islamic thought (Journal of the College of Basic Education, 2022)
The biography of the twelve imams from Ahl al-Bayt  represents the realistic march of Islam after the era of the Messenger, and studying their lives in an assimilated manner reveals to us an assimilated picture of the movement of authentic Islam, which began to make its way into the depths of the nation after its thermal energy began to diminish after the departure of the Noble Messenger , so the imams took The Infallibles  work to educate the nation and mobilize its energies towards finding and escalating the missionary awareness of the Sharia and the movement of the Messenger  and his blessed revolution, not deviating from the path of the universal norms that control the behavior of the leadership and the nation as a whole.